2018
DOI: 10.1080/02699052.2018.1494852
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in brain volumetry and cognitive functions after moderate and severe diffuse axonal injury

Abstract: Our findings suggest that MHL may be a predictor of WMV reduction but cannot predict EF or EVM in DAI. Brain atrophy progresses over time, but patients showed better EF and EVM in some of the tests, which could be due to neuroplasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 69 publications
0
15
0
1
Order By: Relevance
“…[17] SWI was utilized to document an association between total DAI lesion burden and white matter atrophy at 1 year in patients with moderate to severe DAI, although these patients were able to improve their cognitive functioning with rehabilitation. [18] As imaging techniques continue to be refined and the data they generate are analyzed with regard to prognosis, MRI may play a larger role in the clinical management of comatose patients with severe TBI and DAI. The blanket description of Grade 3 for brainstem DAI lesions was of concern in this study as several patients initially assessed as Grade 3 DAI regained consciousness with GCS of 15 before hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…[17] SWI was utilized to document an association between total DAI lesion burden and white matter atrophy at 1 year in patients with moderate to severe DAI, although these patients were able to improve their cognitive functioning with rehabilitation. [18] As imaging techniques continue to be refined and the data they generate are analyzed with regard to prognosis, MRI may play a larger role in the clinical management of comatose patients with severe TBI and DAI. The blanket description of Grade 3 for brainstem DAI lesions was of concern in this study as several patients initially assessed as Grade 3 DAI regained consciousness with GCS of 15 before hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that traumatic brain injury (TBI)—one of the leading causes of death and disability worldwide—leads to greater ‘brain age’ ( Cole et al, 2015 , Gan et al, 2021 ). Atrophy of grey and white matter, alongside other pathological processes, may drive elevated ‘brain age’ in TBI ( Savjani et al, 2017 , Feltrin et al, 2018 , Graham and Sharp, 2019 , Harris et al, 2019 ). Establishing whether TBI leads to a ‘one-off’ loss in cellular volume, progressive, or accelerated ‘brain age’ is of considerable importance to the field and has significant ramifications for patient management.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury results in loss of grey and white brain matter ( Raz et al, 1997 , Fjell et al, 2009 , Douaud et al, 2014 ). However, given that some studies have found progressive loss of brain volume, it has been postulated that TBI may also lead to ongoing, accelerated, ‘brain age’ ( Sidaros et al, 2009 , Cole et al, 2018 , Feltrin et al, 2018 , Harris et al, 2019 ). Progressive changes in brain structure following TBI may be further exacerbated over time through interaction with the neurobiological processes of ageing.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is the first randomized clinical trial to investigate anxiety outcomes after 10 consecutive sessions of high-frequency rTMS in patients with chronic moderate to severe TBI. Due to the high incidence of diffuse lesions in moderate to severe TBI and the widespread non-specific brain lesion damage location (9,67,68), this is an excellent population to investigate the efficacy of rTMS intervention on anxiety symptoms. This study is the result of a post-hoc analysis of a clinical trial that evaluated the effects of rTMS on attention and executive functions (66).…”
Section: Introductionmentioning
confidence: 99%